Health Services Students’ Knowledge of Sexually Transmitted Diseases - Akbaba, Özge; Demirtürk Selçuk, Ezgi (UI Scholars Hub, 2024)
Background: The rising incidence of sexually transmitted diseases (STDs) among young people is a significant public health issue. This study aims to assess the level of knowledge of sexually transmitted diseases among students at a vocational health school. Methods: A descriptive study was conducted at a university in eastern Turkey from January to June 2024. The sample consisted of 621 students who agreed to participate. Data were collected from a sociodemographic form and the Sexually Transmitted Diseases Knowledge Questionnaire. Results: Knowledge was higher among males, second-year students, those in the emergency and disaster management program, those with previous education about STDs, and those familiar with prevention methods (p < 0.05). Human immunodeficiency virus/AIDS was the most commonly recognized disease (64.3%), and 61% of students reported having received information about sexually transmitted diseases at school. Conclusion: The mean total score of the students was 7.11 ± 5.94. The level of knowledge of sexually transmitted diseases is low. Effective educational interventions are essential for future healthcare providers to improve health education and implement preventive measures.